Imaging of rare medullary adrenal tumours in adults. Issue 5 (May 2016) - Maciel, C.A.; Tang, Y.Z.; Coniglio, G.; Sahdev, A.
Abstract : Although adrenal medullary tumours are rare, they have important clinical implications. They form a heterogeneous group of tumours, ranging from benign, non-secretory, incidental masses to hormonally active tumours presenting acutely, or malignant tumours with disseminated disease and a poor prognosis. Increasingly, benign masses are incidentally detected due to the widespread use of imaging and routine medical check-ups. This review aims to illustrate the multimodality imaging appearances of rare adrenal medullary tumours, excluding the more common phaeochromocytomas, with clues to the diagnosis and to summarise relevant epidemiological and clinical data. Careful correlation of clinical presentation, hormone profile, and various imaging techniques narrow the differential diagnosis. Image-guided percutaneous adrenal biopsy can provide a definitive diagnosis, allowing for conservative management in selected cases. A close collaboration between the radiologist, endocrinologist, and surgeon is of the utmost importance in the management of these tumours.